Cellular development and evolution of the mammalian cerebellum [research data] - Sepp, Mari; Leiss, Kevin; Sarropoulos, Ioannis; Murat, Florent; Okonechnikov, Konstantin; Joshi, Piyush; Leushkin, Evgeny; Mbengue, Noe; Schneider, Céline; Schmidt, Julia; Trost, Nils; Spänig, Lisa; et al. (Universität, 2021)
The expansion of the neocortex, one of the hallmarks of mammalian evolution was accompanied by an increase in the number of cerebellar neurons. How...
Grant information: European Research Council: 615253, OntoTransEvol, European Research Council: 819894, BRAIN-MATCH, Brain Research Program: 2017-1.2.1-NKP-2017-00002, Cancer Research UK: FC011171, UK Medical Research Council: FC011171, Wellcome Trust: FC011171
Kind of data: Single nucleus transcripomes
Gesehen am 13.12.2021
Keywords: Forschungsdaten; Datenbank